2017
DOI: 10.1039/c6ra25739a
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured surfaces of biodegradable silica fibers enhance directed amoeboid cell migration in a microtubule-dependent process

Abstract: Cell motion and in particular amoeboid migration is crucial for the survival of living organisms. To advance biomedical research, a constant need for novel materials and surface structures arises, improving immigration of cells into artificial structures used for tissue engineering and for advancing therapy in modern medicine. This work focuses on investigating amoeboid single-cell migration on intrinsically nano-structured, biodegradable silica fibers in comparison to chemically equivalent plain glass surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The cellular response to nano/micrometre-sized fibres, grooves, pillars and contact-printed lines has been well documented, demonstrating the role of contact guidance and topographical guidance by nano-and microscale geometrical features in cell migration [6,[16][17][18][19][20][21][22][23][24][25]. Moreover, there is a growing body of evidence that cells can also respond to geometrical cues equal or even larger than cell size [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The cellular response to nano/micrometre-sized fibres, grooves, pillars and contact-printed lines has been well documented, demonstrating the role of contact guidance and topographical guidance by nano-and microscale geometrical features in cell migration [6,[16][17][18][19][20][21][22][23][24][25]. Moreover, there is a growing body of evidence that cells can also respond to geometrical cues equal or even larger than cell size [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…While proliferation is highly diminished or even stopped on all samples, a high number of cells detaches from nanoporous samples while cells on FLAT samples remain adherent. In a recently published study, we found that the microtubule‐diminishing drug Benomyl has a similar effect on the adhesion of amoeboid cells of Dictyostelium discoideum to nanostructured SiO 2 fibers: Upon drug treatment, almost all of the cells deadhere from the nanostructured fibers, adhesion to flat glass is persisting. [ 45 ] These findings indicate a suitability of these nanoporous substrates for the quick detection of active substances that interfere with cytoskeletal and adhesion processes. This or similar effects found in future studies could be fostered for clinical application, e.g., in personalized cancer treatments to see if a specific patient's cancer cells respond differently to a set of potential drugs or drug combinations.…”
Section: Discussionmentioning
confidence: 94%
“…Proliferation Experiments: Prior to the experiments, nanoporous glass membranes with four different mean pore sizes (17,45,81, and 124 nm) and FLAT glass reference samples were glued to glass sample holders for upside-down culture and autoclaved. The glasses and TCPS reference surfaces were pre-incubated with phosphate buffered saline (PBS, Sigma-Aldrich) for 15 min and culture medium for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the natural ECM, this is enabled by the loosely intertwined, yet mechanically strong, densely packed extracellular matrix proteins. Since cells are capable of sensing this environment with submicron resolution, 7 and are highly influenced by the 2D and 3D morphology of the substrate, 8,9 a scaffold fabrication technique with corresponding submicron resolution is needed. Several rapid prototyping methods were established within recent years for the generation of 3D scaffolds for cell support.…”
Section: New Conceptsmentioning
confidence: 99%